Analysis of the presence of pathogenic microorganisms in makeup: literature review (Research, Society and Development, 2021)
This article aims to analyze scientific studies that evaluated the presence of pathogenic microorganisms in cosmetics. Thus, a literature review was carried out, based on scielo databases, academic google, Transdisciplinary Health Seminar, Journal of basic and applied pharmaceutical sciences, among other data sources, published in Portuguese and English. Cosmetics are preparations composed of natural or synthetic substances that can be used externally in various parts of the human body, and are intended to clean, add fragrance, change their appearance or correct body odor. Some makeup can cause adverse reactions to users. These effects can usually be caused by personal factors such as physiological or by improper use of the product, therefore, biological tests for safety evaluation must be carried out before the cosmetics are placed on the market. The guarantee in the quality of cosmetics is an extremely important factor with regard to skin health. Several microorganisms, pathogens or not, can be present in cosmetic formulations, but the presence of other microorganisms from the constant and even improper use of these cosmetics can lead to an imbalance of the cosmetic skin microflora. It is concluded, from the results of this study, the presence of bacteria of the Staphylococcus group in cosmetics, which are subdivided into: aureus and epidermidis. Such bacteria can harm human health, ranging from simple to more complex infections due to the fact that cosmetics are non-sterile products.